1981
DOI: 10.1104/pp.68.2.284
|View full text |Cite
|
Sign up to set email alerts
|

Two Kinds of Protein Glycosylation in a Cell-Free Preparation from Developing Cotyledons of Phaseolus vulgaris

Abstract: Membrane preparations from developing cotyledons of red kidney bean (Phaseolas vulgaris L) transferred radioactive mannose from GDP-mannose (U-I'4Clmannose) to endogenous acceptor proteins. The transfer was inhibited by the antibiotic tunicamycin, suggesting the involvement of lipidoLigosaccharide intermediates typical of the pathway for glycosylation of asparagine residues. This was supported by the similarity of the linkage types of radioactive mannose in lipid-oligosaccharide and glycoprotein products; both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1

Year Published

1982
1982
1991
1991

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 14 publications
(30 reference statements)
1
8
1
Order By: Relevance
“…Most of the radioactivity was in the polypeptides of phaseolin and PHA, whether the organelle fraction was labeled in vitro with UDP-GlcNAc, or the cotyledons were labeled in vivo with GlcNAc. That the in vitro incorporation was mostly in PHA and phaseolin was confirmed by immunoaffinity chromatography using antibodies to PHA and phaseolin (data not shown) as was demonstrated by Davies and Delmer (3). It is obvious from Figure 1 that there is differential labeling of the individual polypeptides.…”
supporting
confidence: 55%
“…Most of the radioactivity was in the polypeptides of phaseolin and PHA, whether the organelle fraction was labeled in vitro with UDP-GlcNAc, or the cotyledons were labeled in vivo with GlcNAc. That the in vitro incorporation was mostly in PHA and phaseolin was confirmed by immunoaffinity chromatography using antibodies to PHA and phaseolin (data not shown) as was demonstrated by Davies and Delmer (3). It is obvious from Figure 1 that there is differential labeling of the individual polypeptides.…”
supporting
confidence: 55%
“…9. A glycosyltransferase that transfers G1cNAc residues from UDP G1cNAc to mannosyl residues of PHA and phaseolin has been shown to be associated with the membranous organelles of P. vulgaris cotyledons (24). When membranous organelle fractions were incubated with labeled UDP-G1cNAc it was found that most of the GIcNAc that became incorporated into phaseolin and PHA was terminal G1cNAc.…”
Section: Gpz Is Formed By the Removal Of The Terminal Gicnac Residuesmentioning
confidence: 99%
“…Phaseolin is a glycoprotein with high-mannose oligosaccaride sidechains which are susceptible to removal by endo-fl-N-acetyl glucosaminidase H (6,18). Some phaseolin polypeptides have only one high-mannose sidechain, while others have two (8).…”
Section: Introductionmentioning
confidence: 99%